A multifunctional poly-N-vinylcarbazole interlayer in perovskite solar cells for high stability and efficiency: a test with new triazatruxene-based hole transporting materials. Issue 5 (12th January 2017) - Su, Pei-Yang; Huang, Li-Bo; Liu, Jun-Min; Chen, Yi-Fan; Xiao, Li-Min; Kuang, Dai-Bin; Mayor, Marcel; Su, Cheng-Yong
Abstract : Coupling of a polymer-protection method with the molecular design of a novel HTM in PSCs: a PVK-protection approach and triazatruxene-based HTMs are developed. Abstract : The hydrophobic and conductive polymer poly- N -vinylcarbazole (PVK) has been successfully utilized as a multifunctional interlayer between perovskite and the hole transporting material (HTM) for highly stable and efficient perovskite solar cells (PSCs) for the first time. The very thin PVK interlayer can not only protect the perovskite structure from moisture and degradation, but also modulate the interface to reduce charge recombination and promote hole transportation simultaneously. Benefited by coupling this PVK-protection method with the molecular design of an economical and synthetically facile triazatruxene-based HTM (SP-12 ) featuring good stability, planarity and hole mobility, a reliable power conversion efficiency of 18.8% has been achieved, which is superior to that using the well-studied spiro-OMeTAD (16.9%), demonstrating a promising fabrication approach to efficient and long-term stable PSCs.